2023
DOI: 10.3390/bioengineering10030347
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering for the Microbial Degradation of Petroleum Hydrocarbon Contaminants

Abstract: Petroleum hydrocarbons are relatively recalcitrant compounds, and as contaminants, they are one of the most serious environmental problems. n-Alkanes are important constituents of petroleum hydrocarbons. Advances in synthetic biology and metabolic engineering strategies have made n-alkane biodegradation more designable and maneuverable for solving environmental pollution problems. In the microbial degradation of n-alkanes, more and more degradation pathways, related genes, microbes, and alkane hydroxylases hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 162 publications
0
3
0
Order By: Relevance
“…Petroleum hydrocarbons are categorized as alkanes, cycloalkanes, and aromatics. Alkanes, as non-polar compounds, are an important part of petroleum hydrocarbons [6]. The results of our testing and analysis of the composition and content of petroleum hydrocarbon contamination at the site found that alkanes accounted for the highest percentage of total petroleum hydrocarbons in groundwater, with an average of 65.6% of the total oil percentage, specifically including dodecane and pentadecane.…”
Section: Introductionmentioning
confidence: 80%
“…Petroleum hydrocarbons are categorized as alkanes, cycloalkanes, and aromatics. Alkanes, as non-polar compounds, are an important part of petroleum hydrocarbons [6]. The results of our testing and analysis of the composition and content of petroleum hydrocarbon contamination at the site found that alkanes accounted for the highest percentage of total petroleum hydrocarbons in groundwater, with an average of 65.6% of the total oil percentage, specifically including dodecane and pentadecane.…”
Section: Introductionmentioning
confidence: 80%
“…Their surfactant properties enable them to solubilize and enhance the bioavailability of hydrophobic pollutants (Figure 2), aiding in the removal or degradation of contaminants in soil and water environments [103]. Iturin compounds, particularly iturin A, have been found to have significant hydrocarbondegrading capabilities [104]. They can break down and metabolize hydrocarbon pollutants, such as petroleum hydrocarbons and polycyclic aromatic hydrocarbons (PAHs), which are commonly found in oil spills and industrial pollution.…”
Section: Bioremediationmentioning
confidence: 99%
“…strain TY-5, Acinetobacter sp. and, Falsochrobactrum tianjinense , respectively ( Hu et al 2022 ; Wang et al 2023 ). Additionally, petroleum aromatic compounds degradation mechanisms have also been reported in literature like o-ring cleavage and m-ring cleavage pathways, toluene 4-monooxygenase pathway (TMO), toluene 3-monooxygenase pathway (Tbu), toluene 2-monooxygenase pathway (TOM), toluene dioxygenase pathway (Tod), toluene methyl monooxygenase pathway (TOL) for toluene, salicylate pathway, gentisate pathway, procatechuic acid pathways for naphthalene, anaerobic benzene degradation pathways via methylation, hydroxylation and carboxylation, xylene degradation pathways via phenol hydroxylase, monooxygenase and dioxygenase routes, β-ketoadipic acid pathway of benzoic acid degradation and the novel pathways of toluene and naphthalene degradation involving the cyclohexene, cyclohexane, cyclohexanol and cyclohexanone formation ( Reiner 1971 ; Denome et al 1993 ; Goyal and Zylstra 1997 ; Abu Laban et al 2010 ; Brzeszcz and Kaszycki 2018 ; Di Canito et al 2018 ; Muccee et al 2019 ; Muccee et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%